FORMAREA INIŢIALĂ A PROFESORULUI DE INFORMATICĂ: ASPECTE DIDACTICE - USM ADMIN (Moldova State University, 2010)
In order to correspond to the requirements of a world that is in a permanent change, the profession of the teacher should be developing. In most of the educational systems there are attested substantive changes in the content of the school teacher's training. These changes pursue the change of the teacher's status in the educational system: from the existent status of the executor (of the strategies, methods, didactic techniques, proposed by other people) to the status of a professional, who is capable to analyze the occurred situations and to suggest his/her own solutions regarding the management of these situations. In the article there are analyzed the causes that lead to the necessity of changes in the initial training of the teacher of informatics and there is proposed a didactic model oriented towards the professionalizing training.